Garapan Tari “Akegh Cahayegh”: Representasi Budaya Ritual Pengobatan Tolak Bala Suku Talang Mamak, Desa Gedabu - Suvina Suvina; Martion Martion; Ali Sukri (Dance and Theatre Review, 2020)
The Creation of "Akegh Cahayegh" Dance: The Culture Representation of Medicinal Ritual on Calamity Reversal of Talang Mamak Tribe, Gedabu Village. The Talang Mamak tribe is a group of people included in the KAT category (Remote Indigenous Community), which is another name for the Tribe of Anak Dalam. The Talang Mamak tribe belongs to the Proto Melayu group. The Talang Mamak tribe's life inspires this source of work in the neighborhood where the workmen live. The craftsmen were very interested in the Mahligai treatment (Tolak Bala), which was located in the inland tribal area of Talang Mamak, Gedabu village in Rakit Kulim sub-district—inspired to work on this culture to survive in today's life. The craftsmen certainly feel proud when this culture is preserved and displayed with new cultivation (innovation) without leaving the medicinal ritual's distinctive features. This work was worked on with the results of the interpretation and imagination of the writer. The values contained in this work are the values of loyalty, obedience, and togetherness. The implicit message conveyed is that the development and change of time is not a barrier for the inland tribe of Talang Mamak, Gedabu village to carry out rituals and preserves ceremony, namely the treatment of Mahligai Tolak Bala as a ritual of cleaning the village.Keywords: preserving culture; obeying; togetherness